A tripartite graph based methodology for steady-state solution of generalized multi-mode vapor compression systems. (25th February 2021) - Huang, Ransisi; Aute, Vikrant; Ling, Jiazhen
Highlights: A new solution method for steady state modeling of generalized vapor compression systems. Graph-based tearing algorithm can handle complex systems with multiple operating modes. Verification and validation shown for systems with capacities from 10 to 100 kW. Application presented for reversible heat pumps, VRF, roof-top and supermarket systems. Abstract: The vapor compression system is the dominant technology in providing cooling and heating for residential, commercial, and industrial applications, and thus has significant energy and environmental impact. To predict the steady-state performance of vapor compression systems with a wide variety of configurations and operating modes, a general-purpose representation and solution methodology for vapor compression systems was developed using a component-based simulation architecture. The proposed methodology uses mass flow sign propagation to determine the working fluid flow directions. A tripartite-graph based tearing method was applied to reveal the most efficient component execution order, and to identify the corresponding tearing variables and residual equations. The resulting equations are solved using quasi-Newton method. The representation and solution methods are applied to six test systems: five R410A systems and one CO2 system, with capacities ranging from 10 to 100 kW. The test systems were chosen to represent a wide range of HVAC&R applications and operating modes, including residential heat pump, dual-circuit chiller, vapor injection system, supermarket system, and VRF system. The steady-state solutions of the test systems were verified and/or validated against existing simulations and experimental data. The observed worst case simulation energy imbalance across all cases was 0.91%, and the maximum system performance deviation was 8.94% compared to existing data.